Preference for Object Relative Clauses in Chinese Sentence Comprehension: Evidence From Online Self-Paced Reading Time - Xu, Kunyu; Duann, Jeng-Ren; Hung, Daisy L.; Wu, Denise H. (Frontiers in Psychology, 2019)
Most prior studies have reported that subject-extracted relative clauses (SRCs) are easier to process than object-extracted relative clauses (ORCs). However, whether such an SRC preference is universal across different languages remains an open question. Several reports from Chinese have provided conflicting results; thus, in the present study, we conducted two self-paced reading experiments to examine the comprehension of Chinese relative clauses. The results demonstrated a clear ORC preference that Chinese ORCs were easier to comprehend than Chinese SRCs. These findings were most compatible with the prediction of the integration cost account, which claims that the processing difference between SRCs and ORCs arises at the point of dependency formation. The ORC preference in Chinese poses a challenge to the universality of the SRC preference assumed by the structural distance hypothesis and highlights the values of cross-linguistic research.